The WTO transparency obligations and China - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2018)
When it acceded to the WTO in 2001, China accepted comprehensive transparency obligations as well as substantive commitments covering both market access and rules issues. Initially designed to deal with its opaque trade law regime, the transparency obligations were also expected to help democratize the legislative process and promote the development of the rule of law in China. Now that more than 15 years have passed, an important question is: have the transparency obligations delivered on their original promise? This article answers the question by reviewing how the transparency obligations have worked in practice. It notes that, while transparency has improved in some areas, it is still lacking in other areas. The essay discusses the reasons for the uneven progress, and concludes with some tentative suggestions as to how transparency may be further enhanced.